Considerations Regarding some Transylvanian-Saxon Manuscript Collections from the Folklore Archive of the Sibiu Socio-Human Research Institute - Buzas, Andreea (Ethnographica et Folkloristica Carpathica, 2024)
The archive of the Association of Folklorists and Ethnographers of Sibiu County, currently in the patrimony of the Sibiu Socio-Human Research Institute, was founded in 1977, at the initiative of Professor Ilie Moise. The archive contains collections and recordings, questionnaires, manuscripts, studies and ethnographic works, carried out by more than one hundred researchers of traditional culture in the main folkloric and ethnographic areas of Romania, since 1950 until today. The study presents the most important manuscript collections from the archive's inventory, with a focus on materials of some minorities, especially the Transylvanian Saxons, proof of the cultural interferences so evident in the southern Transylvanian area.